Colonization process determines species diversity via competitive quasi‐exclusion. Issue 9 (16th March 2021) - Yamauchi, Atsushi; Ito, Koichi; Shibasaki, Shota
Abstract: A colonization model provides a useful basis to investigate a role of interspecific competition in species diversity. The model formulates colonization processes of propagules competing for spatially distinct habitats, which is known to result in stable coexistence of multiple species under various trade‐off, for example, competition–colonization and fecundity–mortality trade‐offs. Based on this model, we propose a new theory to explain patterns of species abundance, assuming a trade‐off between competitive ability and fecundity among species. This model makes testable predictions about species positions in the rank abundance diagram under a discrete species competitiveness. The predictions were tested by three data of animal communities, which supported our model, suggesting the importance of interspecific competition in community structure. Our approach provides a new insight into understanding a mechanism of species diversity. Abstract : In the present study, we show that colonization model can explain species diversity in ecological communities, which represents typical trends observed in the rank abundance diagrams (RADs) and provides testable predictions about species positions in the RAD. We test those with three literature data, which indicates that our model may be supported by empirical data. This is a significant study that suggests a mechanism of species diversity based on statistical tests with labeling on RAD.